Education as self-government: the Minhaj Education Society's answer to managing violence in Pakistan. Issue 4 (2nd October 2019) - Jabbar, Naheem; Ali, Usman
ABSTRACT: Development thinking and planning consistently identify religious markers of self-development as inimical to social cohesion in the Global South. Practitioners in the field see any educational philosophy that emphasises the disciplined formation of character by non-secular means as an undesirable reaction to modernisation. Religious or madrasa education is identified as an intrinsically regressive aspect of the indigenous social order that limits the transition to an open-access-order society. Using qualitative data from interviews with the managers of an NGO and a political-reform movement in Pakistan, we explore this conclusion and ask whether the secular norms of citizenship, often insisted upon by the international donor community, are strong enough to challenge residual violence. If they are not strong enough, what resources are available within traditional precepts about self-government such that Pakistanis do not need to learn lessons from Europe to protect minorities from communal predation?